11,000 yrs of environmental change in the Northwest Passage; a multiproxy core record from central Parry Channel, Canadian High Arctic - Pieńkowski, Anna J.; England, John H.; Furze, Mark F.A.; Blasco, Steve; Mudie, Peta J.; MacLean, Brian (My University, 2013)
a rare paleoenvironmental archive from the understudied west-central Canadian Arctic Archipelago. Lithological, biogeochemical, and microfossil (dinoflagellate cysts, non-pollen palynomorphs, benthic and planktonic foraminifera) characteristics, in combination with a chronostratigraphy based on seventeen radiocarbon dates, show seven prominent paleoenvironmental episodes since the end of the last regional glaciation. The basal diamict (Zone I) records decoupling of previously grounded glacial ice, followed by ice-proximal conditions (Zone IIa) commencing at ~ 10.8 cal ka BP (age-depth model extrapolation). After an interval of pervasive sea-ice (Zone IIb), ice-distal conditions are established (Zone IIc). Although sparse microfossils are present in glaciomarine sediments (Zone II), noticeable biological activity with heightened abundances and diversities across all groups begins in the postglacial Zone III (10.3–10.0 cal ka BP) when planktonic foraminifera (Neogloboquadrina pachyderma) appear. As planktonics are excluded from the study area today (due to shallow inter-channel sills), this likely signals the inflow of relatively warm and saline Atlantic-derived Arctic Intermediate Water below 250 m, presumably facilitated by glacio-isostatically enhanced deglacial water depths. The subsequent Zone IV (10.0–7.0 cal ka BP), characterized by heightened biological productivity in both plankton and benthos and reduced seasonal sea-ice cover, may correspond to a previously proposed Holocene Thermal Maximum. This apparent amelioration ends by the mid Holocene (Zone V; 7.0–5.7 cal ka BP) when Arctic Intermediate Water is excluded from the study area and water depths approach modern values. High-Arctic conditions with seasonal sea-ice cover, a circulation dominated by Arctic Ocean Surface Water, and microfossil assemblages similar to modern are found from ~ 5.7 cal ka BP onwards (Zones VI–VII). As only minor environmental fluctuations are apparent during the late Holocene, shorter-term climatic episodes (e.g. Little Ice Age) are not recognized in this record.